Induction of Orthotrops in Vegetatively Propagated Nutmeg (Myristica fragrans Houtt.) Plants. - Rani T G (Department of Plantation Crops and Spices, College of Horticulture, 1994)
Investigations were made to induce orthotrops in vegetatively propagated nutmeg (Myristica fragrans Houtt.) plants at the Department of plantation Crops and Spices, college of Horticulture , vellanikkara, Thrissur during the period 1993-94. Budding orthotropic scions on there year old nutmeg plants alone showed bud take. In situ budding on three year old field plants gave the maximum bud take and bud sprouting . Among the different methods tried , maximum initial success was obtained with patch method in M. fragrans and forkert method in M. beddomei. The month of August was found to be the best season for in situ budding and July for budding in polybag plants. Partial shade was found ideal for better bud take than the mist . chamber conditions in nutmeg. Stumping the root stock above the bud union retaining the whorl of lower leaves gave better sprouting and later survival. The anatomical studies of bud union revealed the sequence of bud union as the callus formation stages , callus bridge stage and cambial differentiation stage. Absence of callusing , damage to cambial layers of stock or scion, thick necrotic layer and a wide gap between stock and scion and phenolic exudation were attributed to the probable reasons for bud failure . On mature branches of nutmeg trees, maximum number of orthotrops were induced when an orthotrop was cut close to the tree trunk leaving 30 cm stump. Staking the immature brown shoots of one to two years age and young green shoots of less than six months of nutmeg grafts acquired a reduced angle with the vertical even one month after removal of stake. Among the physical and chemical treatments tried to induce orthotrops in nutmeg grafts of plagiotropic nature, the treatments stumping and application of 5 ppm kinetin was found superior with respect to the number of shoots produced per plant. However , none of the shoots were found to have orthotropic growth pattern. Anatomy of orthotropic and staked stems revealed the production of more wood towards the adaxial side than towards the adaxial side. Plagiotropic stem have more or less proportionate wood formation on both sides.